Reinventing virtual events : how to turn ghost webinars into hybrid go-to-market simulations that drive explosive attendance - Michael, Justin; Nimchinski, Julia (John Wiley & Sons, Inc., 2023)
"GTM Games creates hybrid events that are compelling and use innovative techniques like mash-ups and role reversals. It's invite only and membership based. This book will be a playbook on how to revamp and innovate with virtual events by an in-demand company making waves in this space. Julia invented Go-To-Market cross-training, and it started a movement. Professionals traded roles and lives in interactive drills vs. flat webinar panels. The NTS pyramid of learning speaks to 90% retention when participants coach and teach each other in a real-world scenario vs. the prevailing status net flicks. At any moment, an audience member could be dropped into the drills. Competitors pitched sponsors. Venture Capitalists made cameos. Justin and Julia experimented with hybrid event structures that had never been seen before. The authors plan to share a blueprint of these secrets, strategies, and tactics exclusively in this playbook. This revolutionary book is not just a modern event manual being touted by some corporations to sell you software. They will reveal their secrets to generate one of the most commercially successful online series. The authors have already generated support and revenue from billion-dollar unicorns as sponsors (Outreach, ZoomInfo, Gong, Drift, 6sense) and featured bestselling authors with millions in book sales and audience. Examples include Oren Klaff (Pitch Anything), LataneÌ¹ Conant, Aaron Ross (Predictable Revenue), Alice Heiman, Andy Paul (Real-Time Selling), and Mike Bosworth (Solution Selling)."--